Investigating the terminological relationships in mystical motifs - Rahman Barzegar, Bahman Nozhat, Fatemeh Modaresi, (Opción, 2019)
Mawlawī was an initiator poet who used all linguistic capacities for mystical esoteric interpretations. In the present study the relationship among three terms has been investigated based on word selection on the basis of mystical motifs. The results of the study showed that concerning the mythical and religious background of the term Khorshid (meaning sun), Mawlawī mixed it with mystical insight of the term Shams (literary meaning sun; also referred to Shams Tabrizi). By the same interpretation Shams is the means by which Mawlawī joins God.